Options for Benchmarking Infrastructure Performance - Pisu, Mauro (OECD Economics Department Working Papers, 2012)
Three main approaches can be used to assess infrastructure performance. The first employs macro-econometric techniques to estimate the impact of the existing infrastructure capital stock on growth and to infer its growth-maximising level. This approach neglects the impact of infrastructure on some dimensions of social welfare, such as pollution. The second relies on ex-ante or ex-post cost-benefit analyses of infrastructure projects. These take into account desirable and undesirable outcomes and provide thus a welfare perspective, but this approach would not allow comparing the performance of the existing infrastructure stock. A third approach aims at benchmarking the social efficiency of infrastructure service provision based on the existing capital stock taking into account positive and negative externalities. This paper analyses the challenges in implementing these approaches